PJMHS 2022
DOI: 10.53350/pjmhs22162956
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison of Endoscopic Third Ventriculostomy Versus Ventriculoperitoneal Shunt in Obstructive Hydrocephalus

Abstract: Objective: The aim of this study is to compare the outcomes of endoscopic third ventriculostomy versus ventriculoperitoneal shunt in Obstructive Hydrocephalus. Study Design: Randomized/Control study Place and Duration: Neurosurgery Department, Mardan Medical Complex, Mardan for the duration 04 years from April 2017 to April 2021. Methods: Sixty individuals of both sexes were brought in for consultation. Involved individuals had hydrocephalus that blocked their airways. The written consent of every patient allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Four studies reported incomplete reporting of outcomes, hence introducing “some concerns” and “high risk of bias” limitation of the overall quality and reliability of the evidence synthesised in this review and meta-analysis [ 1 , 6 , 9 , 11 ]. Further, four studies were found to have “some concerns” in terms of the randomisation process which again may introduce reduced generalisability of our findings [ 1 , 9 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported incomplete reporting of outcomes, hence introducing “some concerns” and “high risk of bias” limitation of the overall quality and reliability of the evidence synthesised in this review and meta-analysis [ 1 , 6 , 9 , 11 ]. Further, four studies were found to have “some concerns” in terms of the randomisation process which again may introduce reduced generalisability of our findings [ 1 , 9 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Ul Haq et al reported the occurrence of one bleeding in each group of patients. 15 Even though we found no significant difference in intraoperative or postoperative bleeding events, patients who underwent VPS had clinically more severe bleedings, due to a higher occurrence of subdural and epidural hematomas, the need for new interventions, and even one death reported by Rahman et al 14 In the previous meta-analysis, there was a significant difference regarding postoperative bleeding. 6 However, some bleedings that were considered postoperative for the previous statistical analysis are inconsistent: the bleeding reported in the VPS group in Navaei et al was intraoperative; the bleeding reported in the ETV group in El-Ghandour was intraoperative and the bleeding reported in the VPS group in Kamikawa et al was not specified.…”
Section: Discussionmentioning
confidence: 51%
“…2C), in accordance with all included studies. 4,5,[13][14][15] Blockage Rate There was a significant increase in blockage ratio in the VPStreated group (RR: 0.15; 95% CI: 0.03-0.75; p ¼ 0.02; I 2 ¼ 53%; ►Fig. 3A).…”
Section: Postoperative or Intraoperative Bleedingmentioning
confidence: 95%
See 2 more Smart Citations